Stylistic Approach In Developing Literary Appreciation Skills Among Students Of Arabic Language Departments In The Subject Of Modern Literature (Journal of the College of Basic Education, 2024)
And sentimentality, in addition to helping the learner analyze literary texts, and thus this research aimed to reveal the development of these skills. The researcher used a critical approach that helps to develop them when analyzing literary texts, which is the stylistic approach. The procedures of the experimental approach were followed, as the researcher adopted an experimental design. It is partially controlled, and the researcher randomly selected his research sample, which consisted of (91) male and female students from the College of Education for Human Sciences / University of Karbala, with (45) students A female student from Section (C) and (46) male and female students from Section (A). Then the researcher rewarded the students of the two groups in the following variables: (chronological age calculated in months, the academic achievement of the parents, and a test of tribal literary appreciation skills). As for the research tool, he prepared The researcher conducted a test to measure the development of literary appreciation skills, which consisted of (40) objective items i t was a multiple-choice type, and after presenting it to a group of arbitrators in the Arabic language curricula, teaching methods, and educational and psychological sciences, its validity and reliability, its difficulty factor, its discriminatory power, and the effectiveness of the incorrect alternatives were verified. After processing the data statistically using a set of statistical methods, it was concluded The researcher found a statistically significant difference in the test of literary appreciation skills in favor of the experimental group at a significance level of (0.05). In light of the research results, the researcher concluded that activating the role of the stylistic approach in analyzing literary texts leads to the development of literary appreciation skill.